Corona-Virus Pandemic: Time of Collaboration in Business - A. A. Nikonorova; A. G. Luchkin; V. A. Melnikov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies issues dealing with one of the most popular trends of supporting business in crisis, i. e. collaboration. Corona-virus pandemic motivated executives to develop creative potential of their employees, to extend horizons of functioning and to start new projects. Collaborations became a popular way of searching for ideas aimed at supporting business. As a rule, companies of different industries participate in collaborations. Each of these companies specializes in certain direction and uses only limited resources, while after integration they get an opportunity to work in new industries. The more participants differ in their functioning and business-models, the more interesting and effective cooperation becomes. The review of collaboration practices founded in Russian business in the current epidemic situation served as a basis of the research. Cooperation with other brands and ability to form effective collaborations, which attract new clients, played a special role in the development of business during the pandemic. Practical experience showed that joint projects helped companies increase profits, attract new audience and step up customer loyalty. These factors gave business an opportunity to stay afloat and partially compensate for losses caused by the pandemic. By amalgamating finance, human and information resources collaboration participants became successful with limited costs. To set a goal and choose a partner was essential.